Perbandingan Rasio Kinerja Bank Syariah Terhadap Pertumbuhan Dana Pihak Ketiga Sebelum Dan Masa Pandemi Covid-19 - Pelisa Pransiska; Dunyati Ilmiah (JPS (Jurnal Perbankan Syariah), 2022)
The purpose of this study was to analyze the effect of performance ratios, namely capital adequacy ratio (CAR), non-performing financing (NPF), and financing to deposit ratio (FDR), on third-party funds (TPF) at Islamic commercial banks (ICB). Then, analyze the performance ratio and growth of TPF before and during the covid-19 pandemic on ICB. The method in this research uses a quantitative approach. Data collection uses secondary data in the form of documentation. The population of this study is all ICB registered with the financial services authority (FSA) for the 2019-2020 period. Sampling in this study uses purposive sampling. The data analysis technique used multiple linear regression analysis and comparison of paired samples. The results showed that partially CAR, NPF, and FDR did not affect the growth of TPF in ICB. However, CAR, NPF, and FDR simultaneously affect the growth of TPF in ICB. Then the comparison results show no difference in CAR, NPF, and FDR before and during the covid-19 pandemic. However, the growth of TPF shows a significant difference before and during the covid-19 pandemic.